2017
DOI: 10.1017/s0007114517001325
|View full text |Cite
|
Sign up to set email alerts
|

Association of flavonoid-rich foods and flavonoids with risk of all-cause mortality

Abstract: 1Flavonoids are bioactive compounds found in foods such as tea, red wine, fruits, and vegetables. 2Higher intakes of specific flavonoids, and flavonoid rich foods, have been linked to reduced 3 mortality from specific vascular diseases and cancers. However, the importance of flavonoid-rich 4 foods, and flavonoids, in preventing all-cause mortality remains uncertain. As such, we 5 examined the association of intake of flavonoid-rich foods and flavonoids with subsequent 6 mortality among 93,145 young and middle-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 35 publications
5
46
3
Order By: Relevance
“…Due to the limited number of studies in the meta-analysis on black tea among men, differences according to gender could not be investigated very well. A recent analysis from the NHS II cohort [ 29 ] reported inverse associations between tea consumption (more than once per week versus nonconsumers) and total, cancer and CVD mortality, but no adjustment was made for coffee intake. It should be noted that the studied contrast in tea intake in NHS II (more than once per week versus nonconsumers) reflects the low tea intake levels in the NHS and is quite different from the levels studied in the NLCS (5+ cups/day versus nonconsumers) reflecting much higher intakes.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limited number of studies in the meta-analysis on black tea among men, differences according to gender could not be investigated very well. A recent analysis from the NHS II cohort [ 29 ] reported inverse associations between tea consumption (more than once per week versus nonconsumers) and total, cancer and CVD mortality, but no adjustment was made for coffee intake. It should be noted that the studied contrast in tea intake in NHS II (more than once per week versus nonconsumers) reflects the low tea intake levels in the NHS and is quite different from the levels studied in the NLCS (5+ cups/day versus nonconsumers) reflecting much higher intakes.…”
Section: Discussionmentioning
confidence: 99%
“…But the strengths of this diet may depend on other components. Characteristic among Japanese diet is the wide consumption of green tea, rich in flavonoids, which are phytochemicals with antioxidant and anticancer properties [ 77 ]. Moreover, high consumption of vegetables, and among them miso soup, containing wakame (Undaria pinnatifida), a healthy sea vegetable, rich in fucoxanthin, a carotenoid has great antioxidant and anticancer activity [ 78 ].…”
Section: Dietary Patterns That Affect Immune Function: Mediterranean mentioning
confidence: 99%
“…Epidemiological studies have indicated that high intake of dietary polyphenols is associated with lower risk for multiple diseases (Kuriyama et al, 2006;Ivey et al, 2017). Based on chemical structures, there are four groups of polyphenols, i.e.…”
Section: Introductionmentioning
confidence: 99%